Antimicrobial and Antitumor Photodynamic Effects of Phleichrome from the Phytopathogenic Fungus Cladosporium Phlei. Issue 4 (2nd October 2018) - So, Kum-Kang; Chun, Jeesun; Kim, Dae-Hyuk
Abstract: Fungal perylenequinones have photodynamic activity and are promising photosensitizers for photodynamic therapy (PDT). Here, we investigated the bactericidal and antitumor activities of phleichrome from the fungal perylenequinone family in vitro . Photodynamic bactericidal activity of phleichrome was analyzed by agar-well diffusion method under dark and illuminated conditions. The photodynamic antitumor activity of phleichrome was analyzed in MCF-7, HeLa, SW480, and HepG2 human cancer cell lines using in vitro cytotoxicity assays. Photodynamic bactericidal activities against Gram-negative and Gram-positive bacteria were species-specific. Antitumor activity against all tumor cell lines increased under the illuminated condition. Depending on the results of the analyses, Phleichrome has potential for further drug development related to its antibacterial and antitumor activities.